Effect of freezing on recombinant hepatitis E vaccine. Issue 7 (2nd July 2020) - Li, Kelei; Dong, Fangyu; Gao, Fan; Bian, Lianlian; Sun, Shiyang; Du, Ruixiao; Hu, Yalin; Mao, Qunying; Zheng, Haifa; Wu, Xing; Liang, Zhenglun
ABSTRACT: Studies have revealed that vaccines are more often exposed to sub-zero temperatures during cold chain transportation than what was previously known. Such exposure might be detrimental to the potency of temperature-sensitive vaccines. The aim of this study was to evaluate the impact of exposure to freezing on the physicochemical properties and biological activities of recombinant hepatitis E (rHE) vaccine. Changes in rHE vaccine due to freezing temperatures were analyzed with regard to sedimentation rate, antigenicity, and antibody affinity and potency. The freezing temperature of rHE was measured, then rHE vaccine was exposed to freezing temperatures below −10°C.Significant increase of sedimentation rate was noted, according to shake test and massed precipitates. In addition, the binding affinity of rHE vaccine to six specific monoclonal antibodies was significantly reduced and the in vivo potency for eliciting a protective IgG response was also partially lost, especially for anti-HEV neutralizing antibodies. Altogether, our work indicates that exposure of rHE vaccine to a temperature below −10°C results in the loss of structural integrity and biological potency of rHE vaccine.